KONSUMERISME DI KALANGAN PENGGEMAR GRUP IDOLA â KAT-TUN DI INDONESIA - , DESLYANA ESA KHARISMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis examine consumerism of Japanese idol group â KAT-TUNâs fans in Indonesia. The purpose of this study is to explain the reason why fans loves KAT-TUN as an Idol, the consumerism of fans it self, and the impact from those activity. This research analisis is using qualitative methode that based on consumer cultureâs theory. Based on the reasearch result, it has discovered that the reason of Indonesianâs fans loves KAT-TUN are from their unique musics and from their characteristics. From the result of the research, they using around 30% from their main income for buying KAT-TUNâs official goods like CD, DVD, magazine, and more. Moreover, they using about 8% from their main income for internet needs. The positive value from this activity are, they got a lot of friends, motivated, inspired, learn Japanese culture and languange, and as media entertainment. While the negative value from this activity are emergence ofexcessiveconsumption and fanaticsm. Key words: consumer culture, idol group, fans.